2021
DOI: 10.1073/pnas.2016580118
|View full text |Cite
|
Sign up to set email alerts
|

Expansions of adaptive-like NK cells with a tissue-resident phenotype in human lung and blood

Abstract: Human adaptive-like “memory” CD56dimCD16+ natural killer (NK) cells in peripheral blood from cytomegalovirus-seropositive individuals have been extensively investigated in recent years and are currently explored as a treatment strategy for hematological cancers. However, treatment of solid tumors remains limited due to insufficient NK cell tumor infiltration, and it is unknown whether large expansions of adaptive-like NK cells that are equipped for tissue residency and tumor homing exist in peripheral tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 56 publications
4
75
0
Order By: Relevance
“…In recent years, it has been reported that NK cells can be converted to ILC1-like cells, which display poorer cytotoxic capabilities ( 60 ), as evident from reduced control over tumour burden and metastasis ( 61 , 62 ). Distinct from NK cells, the ILC1s do not express Eomes ( 60 ), further implicating this T-box transcription factor in marking functional and mature NK cells rather than its less cytotoxic ILC1 counterpart.…”
Section: Role Of T-box Transcription Factors In Cell Phenotype and Function: Parallels In Nk And T Cellsmentioning
confidence: 99%
“…In recent years, it has been reported that NK cells can be converted to ILC1-like cells, which display poorer cytotoxic capabilities ( 60 ), as evident from reduced control over tumour burden and metastasis ( 61 , 62 ). Distinct from NK cells, the ILC1s do not express Eomes ( 60 ), further implicating this T-box transcription factor in marking functional and mature NK cells rather than its less cytotoxic ILC1 counterpart.…”
Section: Role Of T-box Transcription Factors In Cell Phenotype and Function: Parallels In Nk And T Cellsmentioning
confidence: 99%
“…Recent studies have revealed that NK cells are highly heterogeneous with different immune functions [25][26][27] .…”
Section: Il-12 Immunotherapy Prompts Nk Cells To Orchestrate An Anti-tumor Microenvironmentmentioning
confidence: 99%
“…Liver tissue is enriched with innate immune cells that can effectively and quickly defend against invading microorganisms and tumor transformation (3)(4)(5). Lymphocytes are classically viewed as continuously circulating in peripheral organs; however, recent studies demonstrate the existence of tissue-resident lymphocytes in the skin, lung, and intestinal mucosa and other peripheral organs, where they exert protective immunity to infection and malignancy (6)(7)(8)(9). Notably, the liver contains multiple resident lymphocytes including memory CD8 + T (T RM ) cells, invariant natural killer T (iNKT) cells, mucosal-associated invariant T (MAIT) cells, and natural killer (NK) cells (10,11).…”
Section: Introductionmentioning
confidence: 99%